The effect of celebrity endorsement on consumer purchase intention - Thamrin Thamrin; Rizki Ozi Ramadhan (Universitas Negeri Padang, 2021)
Purpose of this research are to analyze: (1) The influences of celebrity attractiveness toward purchase intention, (2) The influences of celebrity trustworthiness toward purchase intention, (3) The influences of celebrity expertise toward purchase intention, (4) The influence of celebrity attractiveness, celebrity trustworthiness, celebrity expertise simultaneously toward purchase intention. The research aims to determine the effect of celebrity endorsement toward purchase intention of Adidas products. This research was conducted on 199 respondent who have used intention to purchase Adidas product. The analytical method used is a structural equation model (SEM) with SPSS analysis. Based on the results of data processing that has been found, the results of hypothesis testing found that celebrity endorsement has an effect on purchase intenton Adidas customers.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//